Association of Methylenetetrahydrofolate Dehydrogenase 1 Polymorphisms with Cancer: A Meta-Analysis - Zhang, Hongtuan (Public Library of Science, 2013)
BACKGROUND: Studies investigating the association between single-nucleotide polymorphisms (SNPs) of the methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) and cancer risk report conflicting results. To derive a more precise estimation of the relationship between MTHFD1 polymorphisms and cancer risk, the present meta-analysis was carried out. METHODOLOGY/PRINCIPAL FINDINGS: A comprehensive search was conducted to determine all the eligible studies about MTHFD1 polymorphisms and cancer risk. Combined odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association between the MTHFD1 polymorphisms and cancer risk. We investigated by meta-analysis the effects of 2 polymorphisms in MTHFD1: G1958A (17 studies, 12348 cases, 44132 controls) and G401A (20 studies, 8446 cases, 14020 controls). The overall results indicated no major influence of these 2 polymorphisms on cancer risk. For G1958A, a decreased cancer risk was found in acute lymphoblastic leukemia (ALL)/Asians (the dominant: OR = 0.74, 95% CI = 0.58–0.94, P = 0.01; allelic: OR = 0.80, 95% CI = 0.65–0.99, P = 0.04) and other cancers (recessive: OR = 0.80, 95% CI = 0.66–0.96, P = 0.02). For G401A, the data showed that MTHFD1 G401A polymorphism was associated with a decreased colon cancer risk under dominant model (OR = 0.89, 95% CI = 0.80–0.99, P = 0.04). CONCLUSIONS: The results suggest that MTHFD1 G1958A polymorphism might be associated with a decreased risk of ALL and other cancers. Meanwhile, the MTHFD1 G401A might play a protective role in the development of colon cancer. Large-scale and well-designed case-control studies are necessary to validate the risk identified in the present meta-analysis.